Trilemma challenges for the People's Republic of China - Masahiro Kawai; Li-Gang Liu (Asian Development Bank Institute (ADBI), 2015)
This paper first reviews recent developments in exchange rate regimes, capital account liberalization, interest rate liberalization, and monetary policymaking in the People's Republic of China (PRC). It then observes that the PRC's monetary policy autonomy may have been reduced with falling capital control effectiveness and a rigid exchange regime that is still tightly managed against the United States ( US ) dollar. This hypothesis is investigated empirically using both the Taylor rule and the McCallum-like rule to test whether the PRC's money market interest rate and/or quantity of money supply are being increasingly influenced by the US interest rate or reserve accumulation. The paper concludes that there is considerable evidence suggesting diminishing monetary policy autonomy in the PRC. To regain policy autonomy, the monetary authority needs to substantially increase exchange rate flexibility of the renminbi as long as it continues to pursue capital account opening.
Keywords: E52; E58; 330; trilemma challenges; exchange rate regimes; monetary policy autonomy; peoples republic of china; taylor rule; mccallum rule